Fostering Innovation in the Treatment of Chronic Polymicrobial Cystic Fibrosis-Associated Infections Exploring Aspartic Acid and Succinic Acid as Ciprofloxacin Adjuvants - Silva, Eduarda; Monteiro, Rosana; Grainha, Tânia; Alves, Diana; Pereira, Maria Olivia; Sousa, Ana Margarida (Frontiers in Cellular and Infection Microbiology, 2020)
Cystic fibrosis (CF) disease provokes the accumulation of thick and viscous sputum in the lungs, favoring the development of chronic and polymicrobial infections. Pseudomonas aeruginosa is the main bacterium responsible for these chronic infections, and much of the difficulty involved in eradicating it is due to biofilm formation. However, this could be mitigated using adjuvant compounds that help or potentiate the antibiotic action. Therefore, the main goal of this study was to search for substances that function as adjuvants and also as biofilm-controlling compounds, preventing or dismantling P. aeruginosa biofilms formed in an in vitro CF airway environment. Dual combinations of compounds with subinhibitory (1 and 2 mg/L) and inhibitory concentrations (4 mg/L) of ciprofloxacin were tested to inhibit the bacterial growth and biofilm formation (prophylactic approach) and to eradicate 24-h-old P. aeruginosa populations, including planktonic cells and biofilms (treatment approach). Our results revealed that aspartic acid (Asp) and succinic acid (Suc) restored ciprofloxacin action against P. aeruginosa. Suc combined with 2 mg/L of ciprofloxacin (Suc-Cip) was able to eradicate bacteria, and Asp combined with 4 mg/L of ciprofloxacin (Asp–Cip) seemed to eradicate the whole 24-h-old populations, including planktonic cells and biofilms. Based on biomass depletion data, we noted that Asp induced cell death and Suc seemed somehow to block or reduce the expression of ciprofloxacin resistance. As far as we know, this kind of action had not been reported up till now. The presence of Staphylococcus aureus and Burkholderia cenocepacia did not affect the efficacy of the Asp–Cip and Suc–Cip therapies against P. aeruginosa and, also important, P. aeruginosa depletion from polymicrobial communities did not create a window of opportunity for these species to thrive. Rather the contrary, Asp and Suc also improved ciprofloxacin action against B. cenocepacia. Further studies on the cytotoxicity using lung epithelial cells indicated toxicity of Suc–Cip caused by the Suc. In conclusion, we provided evidences that Asp and Suc could be potential ciprofloxacin adjuvants to eradicate P. aeruginosa living within polymicrobial communities. Asp–Cip and Suc–Cip could be promising therapeutic options to cope with CF treatment failures.